Aortic Aneurysms: Vascular Remodeling and Repair - Kaschina, Elena (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Aortic aneurysm is a multifactorial progressive life-threatening disease. Recent surgical treatment and endovascular repair help to prevent aortic ruptures. However, there are no effective pharmacological treatments to limit aneurysm growth. This Special issue, entitled "Aortic Aneurysms: Vascular Remodeling and Repair", represents a collection of articles from innovative scientists that focuses on the recent advances in diagnostics, pathogenesis and therapies of aneurysms. This reprint includes a systematic review and nine original papers on clinical imaging, prognostic methods, genome-wide screening, novel cell signaling pathways and drug targets. We hope that readers will gain a deeper understanding of this topic and enjoy reading this reprint.